Resistance experiments and self-propulsion estimations of Duisburg Test Case at 1/100 scale. Issue 2 (3rd May 2020) - Kinaci, Omer Kemal; Gokce, Metin Kemal; Delen, Cihad
ABSTRACT: In this study, resistance and propulsion characteristics of the Duisburg Test Case (DTC) Post-Panamax Container Ship were investigated experimentally and numerically. The model scale was different from other studies in the literature. First, resistance experiments with uncertainty analysis were carried out in the Ata Nutku Ship Model Testing Laboratory at Istanbul Technical University. Good agreement was found with other experiments conducted at bigger scales. Then; using the experimental resistance results, self-propulsion point was estimated with a quick methodology recently published in the literature. The study was finalized with numerical simulations of bare hull resistance and self-propulsion tests. Comparisons with other studies having different scales or adopting different methods were made and agreements were satisfactory. Robustness of the self-propulsion estimation methodology was noted, considering its easy implementation and accurate predictions. Resistance experiments and propulsion parameters obtained in this study are expected to form a basis for predicting manoeuvring abilities of DTC.